Embodied and arts-integrated languages and literacies education in primary teacher education : Becoming-teachers’ diffractions of opportunities-and-challenges - Jusslin, Sofia; Korpinen, Kaisa; Hannuksela, Riina; Svendler Nielsen, Charlotte (Jyväskylän yliopisto, 2025)
Embodied learning and arts integration have recently gained more attention in research on languages and literacies education. Researchers have stressed that teacher education can act as a catalyst for bringing new perspectives on teaching languages and literacies to school practices. This study builds on a workshop series about embodied and arts-integrated languages and literacies education implemented in primary teacher education in Finland. Engaging with posthumanist and rhizomatic theories, the study explored becoming-teachers’ diffractions of opportunities and challenges in using embodied and arts-integrated teaching approaches in languages and literacies education. The study was methodologically conducted as arts-based research, specifically by creating poems with data as an analytical approach. The opportunities and challenges created friction between each other and became intertwined as opportunities-and-challenges. As such, the becoming-teachers recognized their value and adopted a critical perspective on the teaching approaches. Illustrated with four poems, the analysis indicates that the becoming-teachers’ engagement with these approaches set in motion thoughts about opportunities-and-challenges concerning (un)learning conceptions of teaching and learning languages and literacies; balancing pedagogical acts and realities; the friction of differentiating the teaching; and a mixture of (un)certainties regarding future teaching practices. In conclusion, implications for languages and literacies education, as well as teacher education, are discussed.